How large is the magnitude of fixed-mobile call substitution? Empirical evidence from 16 European countries - Anne-Kathrin Barth; Ulrich Heimeshoff (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2012)
This paper investigates the degree of fixed-mobile call substitution (FMCS). We use quarterly data from 2004 to mid 2010 on 16 mainly Western European countries. By applying dynamic panel data techniques, we are able to estimate short-and long-run elasticities. The own-price and cross-price elasticities found give strong empirical evidence for substitutional effects towards mobile services. In particular, the estimated cross-price elasticities of the mobile price on the fixed line call demand are relatively large compared to other studies.
Keywords: 330; Dynamic Panel Model; Fix-Mobile Substitution; Telecommunication markets